2017
DOI: 10.1016/j.amsu.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of biologic prosthesis: A systematic review and meta-analysis of comparative studies

Abstract: BackgroundBiologic prosthesis (BP) has been reported as a safe alternative to polytetrafluoroethylene (PTFE) in vascular reconstruction. However, efficacy of BP remains controversial. We, therefore, conducted a systematic review to summarize previous available evidences comparing the BP and PTFE in terms of clinical outcomes.Materials and methodsA literature search of the MEDLINE and Scopus was performed to identify comparative studies reporting outcomes of BP, PTFE, and/or autologous veins graft (VG) in vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In these kind of situations, alternative graft usage should be considered. Although ePTFE has been the most preferred prosthesis, the systematic review and meta-analysis by Wilasrusmee et al revealed that there is a 54% higher graft patency in biological grafts compared to ePTFE in femoropopliteal bypass procedures and vascular access grafts 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In these kind of situations, alternative graft usage should be considered. Although ePTFE has been the most preferred prosthesis, the systematic review and meta-analysis by Wilasrusmee et al revealed that there is a 54% higher graft patency in biological grafts compared to ePTFE in femoropopliteal bypass procedures and vascular access grafts 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are no data on large randomized studies. The authors of one metaanalysis published in 2017 have shown that generally, bioprostheses outperform the analogs made of PTFE in long-term patency, however, there is no information available for evidence-based opinion [6].…”
Section: Relevancy Of the Problemmentioning
confidence: 99%
“…The resultant scaffold is ready for cell colonization as a base for tissue engineering constructs or for use as an autonomous entity with potentially high biocompatibility ( 3 ). It is suggested that such vascular scaffolds outperform synthetic vessels in terms of hemocompatibility and provide a more physiological mechanical match between the prosthetic graft and the host artery ( 4 , 5 ). Additionally, they may provide a valuable alternative to small-diameter vessel (<6 mm) autografts, where polymeric vessels are not applicable due to their high thrombogenicity and compliance mismatch ( 3 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%